Osmotic Vesicle Collapse of Sealed Inside–Out Membrane Vesicles From Red Blood Cells - Tiffert, Teresa; Lew, Virgilio L. (Frontiers in Physiology, 2021)
The preparation of plasma membrane vesicles from a large variety of cells has contributed a wealth of information on the identity and vectorial properties of membrane transporters and enzymes. Vesicles from red blood cell (RBC) membranes are generated in media of extremely low tonicity. For functional studies, it is required to suspend the vesicles in higher tonicity media in order to bring the concentrations of the substrates of transporters and enzymes under investigation within the physiological ranges. We investigated the effects of hypertonic transitions on the vesicle morphology using transmission electron microscopy. The results show that hypertonic transitions cause an irreversible osmotic collapse of sealed membrane vesicles. Awareness of the collapsed condition of vesicles during functional studies is critical for the proper interpretation of experimental results.